Preparation of nanosized tin oxide powder by sol-gel method - Choudhary M.; Mishra V.N.; Dwivedi R. (My University, 2025)
Nanosized SnO 2 particles have been synthesized by a simple sol-gel method. The obtained tin oxide powder has been characterized using X-ray powder diffraction, scanning electron microscope, TG-DTA and fourier transform infrared spectroscopy. The result shows that there is the formation rutile type (tetragonal) structure in nanometric range (14.68 nm). Thermogravimetric analysis was executed to confirm that at 400C (the calcination temperature) no further structural changes due to mass loss occur. It is recommended that the thermal analysis should be done in argon gas because nitrogen gas is more reactive. The IR bands are due to different Sn-O or SnO stretching modes and its lattice modes at 615 and 494 cm 1. © 2012 IEEE.